Predictions and Computational Analysis of Novel Chromosomal Type II Toxin Antitoxin Systems in the Human Oral Microbiome - Bazan, Ashraf Abd-el-Raouf (AUC Knowledge Fountain, 2019)
The importance of the human oral microbiome is progressively receiving considerable attention in recent research, serving as a model niche for studying microevolution. The impact of horizontal gene transfer by mobile genetic elements in such environment is the driving force for the mosaic nature of the oral microbiome. However, there is a missing link between the molecular systems interactions responsible for the plasticity of the genomes and the adaptations of the oral microbiome to physiological and pathological changes. The mobile chromosomal type II Toxin Antitoxin Systems (TASs). are known for their effective role in dynamic environment adaptation and stress response. In this study, we predicted and analyzed the genetic diversity and evolution of type II TAS in the oral microbiome of an Egyptian, presumably healthy, individual. 16S rRNA sequencing (submitted to GenBank). showed taxonomic analysis and microbial diversity and species abundance in three samples of supragingival plaque, subgingival plaque and buccal mucosa. Two hundred and seventy-eight type II TAS were identified from sequenced chromosomal genomes of the oral microbiome by means of exhaustive sequence and 3D structure homology, Hidden Markov Modelling and manual domain analysis. Gene family assignment were proposed since majority of the genes were previously annotated as hypothetical proteins. TAS network of the oral microbiome showed highly interconnected centralities which entails the extensive cross talk and intra-regulatory nature. Molecular ecology analysis of the type II TAS using diversity indexes confirms both diversity and relative abundance of these systems in the oral microbiome. Molecular evolutionary phylogenetic maximum likelihood analysis of the type II TAS, using modified Whelan And Goldman (WAG) as best fit evolution model, was performed for the predicted toxin antitoxin systems. Further analysis revealed evidence for the persistence of the toxin antitoxin systems throughout the oral microbiome. Molecular allometric analysis confirms uneven persistent distribution of the type II TAS. This comprehensive study of new chromosomal type II toxin antitoxin systems found in the oral microbiome provides insights on plasticity of the human oral microbiome and its adaptation to change in the host environment.